O-214 Undisturbed embryo culture under High Humidity atmosphere in a time-lapse system increases pregnancy rates. (6th August 2021) - Cerdá, M.D.L.Á. Valera; Albert, C; Bori, L; Marcos, J; Larreategui, Z; Pellicer, A; Meseguer, M
Abstract: Study question: Does culture in high relative humidity conditions (HC) improve pregnancy rates when using a time-lapse system (TLS) and single-step (SS) culture medium? Summary answer: Using an integrated-TLS and SS medium, culture under HC increases the likelihood of embryos to achieve a pregnancy with respect to those cultured in DC. What is known already: Many variables affect embryo development, and need to be precisely tuned in every IVF laboratory, especially inside the incubators. TLS provide stability during embryo culture, which is a well-known key factor for a proper embryo development. The humidity content of culture atmosphere is especially relevant in order to avoid oscillations in culture media osmolality. It has been previously reported that culture under HC has a significant effect on embryo quality and morphokinetics. However, studies assessing the effect of HC in clinical outcome are rare and inconclusive, mostly due to the variability in the incubator device used and insufficient sample size. Study design, size, duration: The present is a retrospective study performed over 1624 ICSI treatments from 3 fertility clinics from December 2017 to October 2020. Zygote cohorts were randomly assigned to dry (N = 794) or humid conditions (N = 830). It includes autologous treatments with (N = 555) and without (N = 368) pre-implantation genetic testing (PGT) and egg donation treatments (N = 701). Following selection by combining morphological and morphokinetic criteria, 1611 mostly single embryo transfers (92%) were performed, 779 from DC and 832 from HC. Participants/materials, setting, methods: Stimulation, oocyte pickup and fertilization were performed according to the standard procedures of the clinic. We used a GERI incubator (Genea Biomedx), with 6 separated chambers for individual patients, 3 of them configured to work in DC, and 3 in HC. Embryos were cultured in specific 16-well GERI trays with single-step Gems ® culture medium (Genea Biomedx). The effect of HC in pregnancy rate was assessed by multivariate logistic regression and Pearson Chi Square Test. Main results and the role of chance: Types of treatment and patient demographics were homogeneously distributed in the two study groups. Mean patient age was 39.88±4.47 years, BMI: 23.54±4.21 Kg/m2 and number of correctly fertilized oocytes: 7.86±3.87. A logistic regression was performed, including other possible affecting factors: ovum age and origin, transfer day, fresh or frozen-warmed embryo transfer, number of transferred embryos and the use of PGT. Said analysis revealed that embryos cultured in HC are more likely to achieve a pregnancy than those cultured in DC (OR = 1.30, 95% CI (1.05-1.59), p =0.014). Pregnancy rate was significantly higher in HC (66.7%) than in DC (60.9%) in the total embryo transfers ( p = 0.017). Pregnancy rate was also higher in HC in fresh embryo transfers (68.6% in HC vs 63.2% in DC; p = 0.133) and frozen-thawed transfers (65.2% in HC vs 59.1% in DC; p = 0.062), although differences were not statistically significant due to the reduced sample size. Stratifying the results, the significant difference remained in transfers belonging to autologous cycles (68.4% HC vs 56.5% in DC; p = 0.030) and in treatments in which PGT was performed (67.1% HC vs 56.0% in DC; p = 0.023), but the difference in egg donation procedures was not statistically significant (66.4% in HC vs 64.7% in DC, p = 0.577). Limitations, reasons for caution: This is a retrospective analysis performed over the clinics' treatments, so it might be compromised by some bias, although multivariable analysis may overcome them. For further assessing the effect of HC in clinical results a prospective controlled study, with a larger sample size could be performed, also comparing life-birth rates. Wider implications of the findings: These results, alongside our previous findings (Valera et al . 2020, Albert et al . 2020), support that HC contributes to optimize embryo development and clinical results in undisturbed culture in TLS with single-step medium. To our knowledge, this is the largest study on the matter and the first performing multivariable analysis. Trial registration number: Not applicable